Narrative Research Study: Market Sentiment As A Trigger For Cryptocurrency Volatility - Hidayatullah, Mahdi; Juniar, Asrid (Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the impact of market sentiment on cryptocurrency price volatility, focusing on the top 50 cryptocurrencies by market capitalization in 2024. Data was collected from CoinMarketCap for the period 2021-2023, and market sentiment is measured using Natural Language Processing on text data from social media (Twitter, Reddit), forums, and news articles. The analysis employs Structural Equation Modeling - Partial Least Squares to examine the relationship between market sentiment and price volatility. The latent variable